(untitled) (Majalah Kedokteran Bandung, 2024)
Response to chemotherapy for breast cancer can be assessed using the CA 15-3 tumor marker, or through histopathological means such as Miller Payne assessment. This study aimed to explore the correlation between CA 15-3 level and histopathological response in locally advanced breast cancer. This is a cross-sectional study measuring CA 15-3 before and after neoadjuvant chemotherapy using the FAC regiment. This study took place in Dr. Hasan Sadikin Hospital Bandung, Indonesia, from January to August 2022. Data on histopathological responses before chemotherapy and after surgery were also collected. Thirty-nine patients were admitted as subjects. Most patients had invasive carcinoma of no special type (79.5%) and luminal B HER 2 molecular subtype (38.5%). A significant decrease in CA 15-3 level after chemotherapy (from 23.54±18.38 ng/ml to 16.30±6.51 ng/mL) was observed. No significant correlation between CA 15-3 level and Miller Payne histopathological responses were found in the subjects.